Efficient certificate‐based aggregate signature scheme for vehicular ad hoc networks. Issue 6 (13th October 2020) - Chen, Jian‐Neng; Huang, Zhen‐Jie; Zhou, Yu‐Ping; Zou, Fu‐Min; Chen, Chien‐Ming; Wu, Jimmy Ming‐Tai; Wu, Tsu‐Yang
Abstract : As vehicle speed is fast and on board units' (OBUs) computing power, storage space, bandwidth and other resources are very limited, the efficiency of message transmission in vehicular ad hoc network is of great concern. Certificate‐based aggregate signature scheme provides a way to combine numerous signatures into one short signature. The authors propose a certificate‐based aggregate signature scheme for vehicular ad hoc networks. In this study, the authors prove that the proposed scheme is secure against forgery attack in the random oracle model and under the computational Diffie–Hellman problem. It is efficient and suitable for vehicular ad hoc networks.